Political News and Early Voter Alienation: Why does not Political Knowledge Lead Early Voters to Use their Right to Vote? - Karim Suryadi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2008)
Early voters whose backgrounds are senior high school level are believed to possess particular political knowledge. However, this group is suspected to be one of the nests of abstainers. Why does not political knowledge lead them to use their right to vote? To answer this question, a survey had been conducted toward 170 senior high school students in Kota Bandung and an intensive interview had been applied to 10 students. Statistical calculation shows that high correlation degree between political news influence and cognitive conception change of the students, but the degree is low to their political attitude. This discrepancy is caused by political news that is provided in newspaper which indirectly relates to the early voters’ need, besides more impressive news diminishing government image than ones discussing election.